In Vitro Degradation and Mechanical Performance of Mg AZ31B for Biodegradable Bone Implant Applications - Saefudin, Slamet; Purnomo; Muhammad Subri; M. Edi Pujianto; Ilham Yustar Afif; Samsudi Raharjo (Advance Sustainable Science Engineering and Technology, 2026)
Magnesium AZ31B is a promising biodegradable implant material due to its mechanical properties comparable to natural bone and its ability to degrade in physiological environments, potentially eliminating the need for secondary surgery. However, its rapid degradation can cause a significant loss of mechanical integrity, limiting its use in load-bearing applications. This study investigates the evolution of mechanical properties and surface characteristics of AZ31B during in-vitro immersion in Simulated Body Fluid (SBF). Tensile tests were conducted on triplicate specimens after immersion for 3, 6, and 9 days, while surface morphology and corrosion products were analyzed using SEM–EDX. In addition, pH variation and mass loss were monitored to evaluate corrosion behavior. The results show a progressive decrease in tensile strength from 279.77 ± 5.30 MPa (0 days) to 167.64 ± 2.31 MPa after 9 days of immersion, representing an overall reduction of approximately 40%. This degradation was accompanied by increased surface corrosion, mass loss, and solution alkalization. These findings provide quantitative insight into the relationship between corrosion progression and mechanical degradation of AZ31B, highlighting its time-dependent performance limitations and the need for surface modification strategies in biodegradable implant applications.